289 Effects of dietary Zn on ewe milk minerals and somatic cell count. (30th November 2020) - Page, Chad M; Murphy, Tom; Taylor, Bret; Julian, Alexis; Whaley, Jaelyn; Woodruff, Kelly; Hummel, Gwendolynn; DeMarco, Claudia; Laverell, Dylan; Cunningham, Hannah; Rule, Daniel; Stewart, Whit C
Abstract: The objectives of the current study were to evaluate the effects of dietary Zn fed at approximately 3 times NRC recommendations on milk Zn concentrations and mammary health. Within Rambouillet (WF) and Hampshire (BF) breeds, ewes were ranked by BW and randomly assigned down the rank into 2 treatment groups: Control (n = 45, 37 mg Zn/kg DM) and Zn treatment (n = 44, 113 mg Zn/kg DM). Treatments were delivered via a ZnSO4 -fortified alfalfa pellet fed at a rate of 0.45 kg/d DM from a RFID-activated automated feeder from approximately 6 wk before to 4 wk after lambing. Ewe milk was collected twice weekly, and analyzed for mineral content (d 0, 10, and 30 of lactation) and somatic cell count (SCC; d 3–5, 6–9, 10–12, 13–16, 17–19, 20–23, 24–26, 27–29, or 30–32). Single-bearing ewes had greater Ca, Mg, and P (P ≤ 0.04) than multiple-bearing ewes. Day of lactation influenced milk Mg, P, and Zn (P < 0.01), and values generally decreased as lactation progressed. Milk Zn was 1.7-fold greater (P < 0.01) for Zn treatment than Control ewes. Milk Ca, Mg, and P were greater for Control than Zn treatment (P ≤ 0.02) ewes. A breed × litter size effect was detected for LogSCC (P = 0.02). Single-bearing WF ewes had lower LogSCC than multiple-bearing WF ewes (5.36 ± 0.09 vs 5.74 ± 0.07; P < 0.01) but litter size did not affect BF ewe LogSCC (5.80 ± 0.08 vs 5.79 ± 0.09; P = 0.92). Day of lactation impacted ewe SCC (P < 0.01), with peak SCC between d 6 and 9, which began to decline as lactation progressed. In conclusion, dietary Zn above NRC recommendations increased milk Zn.